2019
DOI: 10.1007/s10901-019-09717-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations among housing accessibility, housing-related control beliefs and independence in activities of daily living: a cross-sectional study among younger old in Sweden

Abstract: There is some evidence that housing accessibility, external housing-related control beliefs (HCB) and activities of daily living (ADL) are associated in complex ways; however, these pathways have not been explored in younger old. The aim was to assess the role of external HCB in the relationship between housing accessibility and ADL by applying moderation and mediation models. This was a cross-sectional study involving 366 community-living 67-70 years old participants from the Skåne part of the Swedish Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…In previous studies, HCQ showed comparable satisfactory internal consistency of the subscales in 66 -69 and 65 -91 year olds, and good test-retest reliability in 65 -91 year olds in Germany (30); internal consistency in the HHPD baseline sample was acceptable (31). For the current study, the total score combining two scales was dichotomised at 50% cut-off into low (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and high (34-80) external HCB. GSE was assessed by the self-administered 10-item General self-efficacy Scale (32) at T1.…”
Section: Moderators: External Hcb and Gse At T1mentioning
confidence: 63%
See 3 more Smart Citations
“…In previous studies, HCQ showed comparable satisfactory internal consistency of the subscales in 66 -69 and 65 -91 year olds, and good test-retest reliability in 65 -91 year olds in Germany (30); internal consistency in the HHPD baseline sample was acceptable (31). For the current study, the total score combining two scales was dichotomised at 50% cut-off into low (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and high (34-80) external HCB. GSE was assessed by the self-administered 10-item General self-efficacy Scale (32) at T1.…”
Section: Moderators: External Hcb and Gse At T1mentioning
confidence: 63%
“…In the Swedish younger old, no moderating effect of external HCB was found in relation to the ADL Staircase (19). In very old people from Germany and Sweden those with a higher magnitude of accessibility problems and higher external HCB were more dependent in ADL according to ADL Staircase (p-value = 0.10) (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, lower self-efficacy was found to be a barrier for exercising [15], while higher general and balance self-efficacy were associated with more life satisfaction [16] and better walking capacity [17]. There is some evidence that assigning control over one's housing plays a moderating role in the association between housing accessibility problems and ADL in adults 80-89 years old [18], but not in those 67-70 years old [19], which suggests age related differences. Previous studies were cross-sectional and conducted in the general population limiting causal inference and generalizability to vulnerable populations, such as those ageing with specific chronic diseases.…”
Section: Introductionmentioning
confidence: 99%